Things Fall Apart - Achebe, Chinua (Penguin Group, 1958)
Okonkwo is the greatest wrestler and warrior aliv, and his fame spreads throughout West Africa like a bush-fire in the harmathan. But when he accidentally kills a clansman, things begin to fall apart. The Okonkwo returns from exile to find missionaries and colonial governors have arrived in the village. With his world thrown radically off-balance he can only hurtle towards tragedy...
Keywords: Fiction